2021
DOI: 10.3390/pathogens10091125
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on the Antimicrobial Treatment and Chemoprophylaxis of Human Leptospirosis: A Meta-Analysis

Abstract: Background: Leptospirosis is a worldwide zoonotic infection, and its management needs to be refined. This study aims to discern which antibiotic would be the best option to treat leptospirosis disease and analyze the efficacy of chemoprophylaxis regimens to prevent this illness. Methods: systematic review and meta-analysis on the efficacy of antibiotic treatment and chemoprophylaxis of leptospirosis in humans. Results: Ten clinical trials compared an antibiotic treatment with placebo or other antibiotic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Based on the marked morbidity and potential mortality of the disease, and the risk of zoonotic transmission, as recommended for humans by the CDC, 120 dogs with suspected or probable leptospirosis should be treated with appropriate antimicrobials (LOA 12/12) , despite lack of evidence for a clear benefit for affected humans 121 . The optimal antimicrobial treatment for leptospirosis is unknown.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Based on the marked morbidity and potential mortality of the disease, and the risk of zoonotic transmission, as recommended for humans by the CDC, 120 dogs with suspected or probable leptospirosis should be treated with appropriate antimicrobials (LOA 12/12) , despite lack of evidence for a clear benefit for affected humans 121 . The optimal antimicrobial treatment for leptospirosis is unknown.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Patients with severe leptospirosis, which normally manifests as renal and hepatic failure, are administered penicillin G (penicillin G sodium; at a dose of 1.5 million U/6 h) intravenously ( Figure 1 ). It should be used for a week ( Watt et al, 1988 ; Griffith et al, 2006 ; Karpagam and Ganesh, 2020 ; Guzmán Pérez et al, 2021 ). In accordance with reported records, amoxicillin, ampicillin, azithromycin, doxycycline and tetracycline can also be used for the treatment of severe leptospirosis.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…In accordance with reported records, amoxicillin, ampicillin, azithromycin, doxycycline and tetracycline can also be used for the treatment of severe leptospirosis. It is recommended that children and pregnant women avoid the consumption of doxycycline ( Griffith et al, 2006 ; Jamal Khan et al, 2018 ; Gopi et al, 2021 ; Guzmán Pérez et al, 2021 ). Amoxicillin and azithromycin should be administered to children and pregnant women instead of doxycycline ( Haake and Levett, 2015 ; Karpagam and Ganesh, 2020 ; Chacko et al, 2021 ).…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…1 However, studies have found insufficient evidence to show the benefit of using these antibiotics in leptospirosis management, especially in severe disease and disease prevention. 4,5 One meta-analysis of clinical trials showed that penicillin is not significantly different from placebo in reducing mortality or length of hospital stay when used to treat leptospirosis infections. 5 The same study looked into clinical trials on chemoprophylaxis and found that while there was a significant benefit for taking doxycycline upon flood water exposure, none of the usual antibiotic regimens against leptospirosis were beneficial in reducing symptomatic cases.…”
Section: Original Articlementioning
confidence: 99%
“…4,5 One meta-analysis of clinical trials showed that penicillin is not significantly different from placebo in reducing mortality or length of hospital stay when used to treat leptospirosis infections. 5 The same study looked into clinical trials on chemoprophylaxis and found that while there was a significant benefit for taking doxycycline upon flood water exposure, none of the usual antibiotic regimens against leptospirosis were beneficial in reducing symptomatic cases. 5 Another systematic review of clinical trials concluded that based on data on mortality, duration of illness, duration of fever, and need for dialysis, the benefit of currently used antibiotics in treating leptospirosis is unclear.…”
Section: Original Articlementioning
confidence: 99%